BRAIN-SKETCHING TECHNIQUE FOR DESCRIPTIVE TEXT IN IMPROVE WRITING SKILL AT SENIOR HIGH SCHOOL OF UNISMUH MAKASSAR - Akib, Erwin (Lembaga Perpustakaan Unismuh Makassar, 2012)
The research aimed at improving the ability of the Eleventh grade students of Senior High School of Unismuh Makassar in writing descriptive text using the Brain-Sketching Technique. For the purpose, it employed Classroom Action Research in which the researcher worked in planning, implementation, observation, and reflection on the data collected from the teaching and learning process and the students writing products. The method of this research is Classroom Action Research that consists of two cycles. One cycle consisted of four meetings. It means that there were eight meetings for two cycles. This classroom action research was done in Senior High School of Unismuh Makassar for English subject. As subjects in this research is class XI IPA 2 in 2012-2013 academic years which consists of 26 students. Those consisted of 14 women and 12 men. The instruments used were writing test and observation sheet. The study was conducted in diagnostic test, cycle one and cycles two, each cycle was carried out in four meetings.Â The objective of the research was intended to know the improvement of the studentsâ writing ability after using Brain-Sketching Technique at the Eleventh grade students of Senior High School of Unismuh Makassar. The findings indicated that using Brain-Sketching Technique could improve the students ability in writing descriptive text. Before giving implementation the researcher gave the students diagnostic test and the mean score of diagnostic test was 63.90 as classification âfairly goodâ. Then the researcher conducted the first cycle and the second cycles, and the result showed that the students scores in the first and second cycles improved. In the first cycle, the mean score of students was 67.22 as classification âfairly goodâ, meanwhile the mean score of students in the second cycle was 71.41 as classification âgood. It means that the improvement of studentsâ writing ability from D-Test to cycle I was 5.21%, cycle I to cycle II was 6.22%, D- test to cycle II was 11.73%. Keywords: Brain-Sketching, Technique, Descriptive, Text, Writing.Penelitian ini bertujuan untuk meningkatkan kemampuan siswa di kelas XI SMA Unismuh Makassar dalam menulis teks deskriptif dengan menggunakan Teknik Brain-sketsa. Untuk itu, Penelitian melibatkan Penelitian Tindakan Kelas dimana peneliti melaksanakan dalam perencanaan, pelaksanaan, observasi, dan refleksi pada data yang dikumpulkan dari proses belajar mengajar dan produk menulis siswa. Metode penelitian ini adalah Penelitian Tindakan Kelas yang terdiri dari dua siklus. Satu siklus terdiri dari empat pertemuan. Ini berarti bahwa ada delapan pertemuan selama dua siklus. Penelitian tindakan kelas ini dilakukan di SMA Unismuh Makassar untuk pelajaran bahasa Inggris. Sebagai subyek dalam penelitian ini adalah kelas XI IPA 2 pada tahun akademik 2012-2013 yang terdiri dari 26 siswa. Mereka terdiri dari 14 perempuan dan 12 laki-laki. Instrumen yang digunakan adalah tes tertulis dan lembar observasi. Penelitian dilakukan pada tes diagnostik, siklus satu dan siklus dua, masing-masing siklus dilakukan dalam empat pertemuan. Tujuan dari penelitian ini dimaksudkan untuk mengetahui peningkatan kemampuan menulis siswa setelah menggunakan Teknik Brain-sketsa pada siswa di kelas XI SMA Unismuh Makassar. Temuan menunjukkan bahwa menggunakan Teknik Brain-Sketsa dapat meningkatkan kemampuan siswa dalam menulis teks deskriptif. Sebelum memberikan implementasi peneliti memberi siswa tes diagnostik dan nilai rata-rata dari tes diagnostik adalah 63, 90 sebagai klasifikasi